IMPLEMENTASI PERDA NOMOR 12 TAHUN 2011 TERKAIT PEMBANGUNAN KESEJAHTERAAN ANAK PANTI ASUHAN GATOT SOEBROTO SEMARANG - Dimas Fachmi Insan; Soewanto Adhi; Achmad Taufiq (Journal of Politic and Government Studies, 2014)
Social welfare is a state of fulfillment of living for the people , so that they can developthemselves and to carry out social functions that governments , local governments andcommunities in the form of social services that include social rehabilitation , social security ,social empowerment , and social protection ( Law No. 11 of 2009 article 1 and 2 ) .This study aims to examine the government's policy of Semarang in developingcommunity capacity through the construction of an abandoned orphanage. The orphanage is asocial welfare institution that has the responsibility to provide social welfare services toneglected children and various other social problem with implementing sponsorship and poverty, provide replacement services of physical , mental and social well in foster care , so as to obtainample opportunity , appropriate and adequate for the development of his personality as expectedas part of the next generation of the ideals of the nation and as individuals who will participateactively in the field of national development.In the development of child welfare orphanage children who mostly come from waif ,Semarang government provides assistance in two forms , namely in the form of materialassistance that may include money , goods , or groceries , and coaching support in order to createa special skill for both children to foster and orphanage administrators.Semarang City Government should be able to formulate specific local regulationsregarding the construction of the orphanage, both in physical development and educationaldevelopment. So the orphanage in Semarang has its own budget in the construction and built it,and orphanages can also have a clear standard under development goals. With the specialregulations of Semarang City Government can monitor and control the orphanage in the city ofSemarang by looking at the number of orphanages now too many and difficult to monitor.Keywords: Implementation, SocialWelfare, Orphanages